Silicon-carbon negative electrode material and preparation method and application thereof
By using silicon carbon negative materials, the use of silicon -soluble, graphite powder and boric acid polymers to form a chip structure to solve the problem of function failure and safety caused by the volume expansion of silicon -based negative materials in the process of lithium lithium. Has high -efficiency electrochemical properties and cycle life.
Patent Information
- Application Number
- CN202210042731.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-14
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-01-14
AI Technical Summary
The volume expansion of existing silicon-based negative electrode materials during the deintercalation of lithium leads to material detachment, function failure, and safety problems, while poor conductivity reduces battery efficiency.
The use of silicon carbon negative materials, its chemical formula is li-SI@c-RSOT/B, mixed with silicon solids, graphite powder and boric acid polymers, forming a chip structure after heat treatment, improved the surface area and cycle performance, and passed through the passing of the surface area and circulation. Lithium embedded treatment and thermal treatment improve electrochemical performance.
It improves the surface area and electrochemical properties of silicon carbon negative materials, reduces the damage of the material structure of the volume change, extend the cycle life of the battery and improves safety.
Smart Images

Figure CN114335489B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] In recent years, due to the environmental damage caused by the release of certain metals and electrolytes in waste power batteries and the limited resources of lithium-ion batteries, relevant recycling companies have increased the recycling of waste power batteries. Common recyclable materials in waste power batteries are positive electrode materials such as lithium cobalt oxide, lithium iron phosphate and cobalt nickel manganese oxide, collector materials such as copper and aluminum foil, and negative electrode materials such as graphite. Among them, graphite is a key negative electrode material, so it is very important to develop an efficient recycling and reuse process for graphite from scrapped power batteries, which can reduce the impact of mining on the environment and improve the recycling rate of graphite resources.
[0003] The new energy vehicle industry has higher and higher requirements for the power density and service life of power batteries. In power batteries, negative electrode materials with excellent lithium storage performance and environmental friendliness are crucial. Compared with graphite (carbon-based) negative electrode materials, silicon-based negative electrode materials have extremely high theoretical specific capacity. At present, during the process of lithium extraction and insertion of silicon-based negative electrode materials, the volume expansion of silicon will cause the electrode material to detach from the collector, and even cause the silicon itself to pulverize, resulting in the failure of the negative electrode material function. In addition, silicon itself has poor conductivity, which reduces the transmission efficiency of the battery. The volume expansion of silicon will reduce the pores inside the battery and cause the precipitation of metallic lithium, which poses serious safety problems. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a silicon-carbon negative electrode material and a preparation method and application thereof, which solves the problems of large volume change of silicon negative electrode, destruction of material structure, and functional failure of negative electrode, and at the same time realizes the recycling of graphite waste in waste power batteries and improves the efficient utilization value of negative electrode materials.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A silicon-carbon negative electrode material, the general chemical formula of which is Li f - Si@CR s O t / BZ a O b ; R is at least one of zirconium, copper, nickel, cobalt, manganese, chromium, titanium, molybdenum, silver, magnesium, calcium, germanium, tin and antimony; Z is at least one of aluminum, magnesium and zinc, wherein s and t are independently 1, 2, 3, 4 or 5, a=1 or 2, and b=1 or 3.
[0007] Preferably, R is at least one of zirconium, copper, nickel, cobalt, manganese, chromium, titanium, molybdenum and silver.
[0008] Preferably, the Z a O b It is one of Al2O3, MgO and ZnO.
[0009] Preferably, the R s O t It is at least one of ZrO2, NiO, MnO, and CuO.
[0010] Preferably, the silicon-carbon negative electrode material is Li 0.04 - Si@C-CuO / B-MgO、Li 0.03 - Si@C-MnO / B-MgO、Li 0.02 - Si@C-ZrO2 / B-Al2O3、Li 0.02 - At least one of Si@C-NiO / B-Al2O3.
[0011] A method for preparing a silicon-carbon negative electrode material, wherein the method is used to prepare the above-mentioned silicon-carbon negative electrode material.
[0012] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0013] The silica sol, soluble R salt and boric acid polymer are mixed and stirred, and then graphite powder is added and mixed to obtain Si@CR salt / BAP precursor, and then heat treated to obtain Si@CR s O t / B;
[0014] In an electrolytic cell with graphite block as cathode and metal Z as anode, a lithium ion conductor membrane is used to separate the electrolytic cell into two half cells, namely the cathode half cell and the anode half cell. s O t / B is placed in the cathode half tank and powered for electrolysis to carry out lithium insertion treatment, the cathode half tank is separated into solid and liquid, the solid is washed and dried to obtain Li f - Si@CR s O t / B;
[0015] Add lithium source to the electrolyte in the anode half tank, stir, react, separate solid and liquid, take the solid phase and the Li f - Si@CR s O t / B are mixed evenly, and then heat treated to obtain the silicon-carbon negative electrode material.
[0016] Preferably, the graphite block is prepared by the following method: recovering power batteries, pyrolyzing and screening to obtain battery black powder, adding sulfuric acid to adjust the pH, adding a reducing agent for stirring, separating the solid and liquid, washing the solid phase with water, adding a dispersant for mixing, crushing, and pressing to obtain a graphite block.
[0017] Further preferably, the solid-liquid ratio of the battery black powder and sulfuric acid is 100-300 g / L.
[0018] Further preferably, the concentration of sulfuric acid is 1-10 mol / L; more preferably, the concentration of sulfuric acid is 5-10 mol / L.
[0019] Preferably, the reducing agent is at least one of sodium pyrosulfate, potassium pyrosulfate, sodium sulfite, potassium sulfite, sodium thiosulfate, and potassium thiosulfate.
[0020] Further preferably, the solid-to-liquid ratio of the reducing agent to sulfuric acid is 10-100 g / L.
[0021] Further preferably, the dispersant is at least one of protein solution, glycerol and benzoic acid.
[0022] Further preferably, the solid-to-liquid ratio of the solid phase to the dispersant is 30-400 g / L.
[0023] Further preferably, the particle size of the graphite powder is less than 5 μm.
[0024] Preferably, the solid-liquid ratio of the silica sol, graphite and boric acid polymer is (10-50) g: (2-30) g: (0.1-5) ml.
[0025] Preferably, the added amount of R in the soluble R salt is 0.01-0.10 of the total mass of silica sol and graphite.
[0026] Preferably, the soluble R salt is at least one of soluble sulfates, nitrates, phosphates, chlorides and bromides of zirconium, copper, nickel, cobalt, manganese, chromium, titanium, molybdenum, silver, magnesium, calcium, germanium, tin and antimony.
[0027] Preferably, the boronic acid polymer is at least one of 4-boric acid ester-4',4'-dimethyltriphenylamine and B,B'-thiophene[3,2-B]thiophene-2,5-diacylbis[boric acid].
[0028] Preferably, the heat treatment temperature is 200-400° C., and the heat treatment time is 2-6 hours.
[0029] Preferably, the active metal Z is at least one of magnesium, aluminum, manganese and zinc.
[0030] Preferably, the lithium ion conductor membrane is characterized in that only lithium ions can pass through during electrolysis.
[0031] Preferably, the cathode half tank is composed of Si@CR s O t / B material and conductive agent.
[0032] Further preferably, the conductive agent is a mixture of dimethyl ethylene glycol, ethylene carbonate, and lithium hexafluorophosphate in a volume ratio of 1:1.5:1.
[0033] More preferably, the concentration of lithium hexafluorophosphate is 1.5-2 mol / L.
[0034] Further preferably, Si@CR is attached near the cathode potential in the cathode half slot. s O t / B material.
[0035] Further preferably, the Si@CR s O t / The solid-liquid ratio of B material and conductive agent is 10-50g / L.
[0036] Preferably, the cathode and anode potentials are controlled so that the cathode and anode potential difference is >2.5V.
[0037] Preferably, the anode half-cell electrolyte is a lithium silicate solution, and the concentration of the lithium silicate solution is 0.02-0.15 mol / L.
[0038] Further preferably, the lithium silicate is Li2Si5O 11 , at least one of Li8SiO6, Li2SiO3, Li4SiO4, Li6Si2O7, and Li2Si2O5.
[0039] Preferably, the solid phase, Li f -Si@CR s O t The mass ratio of A / B is (0.1-5):100.
[0040] The inventors studied the use of lithium silicate as an electrolyte in a lithium intercalation solution and a lithium source for lithium intercalation treatment. The lithium intercalation treatment can be represented as follows:
[0041] e·1 / jLi j Si k O l +Si@CR s O t / B+f·1 / X·Z→Li f -Si@CR s O t / B+f·1 / X·Z X+ +(ef)1 / jLi j Si k O l .
[0042] Preferably, the heat treatment temperature is 200-400° C., and the heat treatment time is 2-6 hours.
[0043] Preferably, the heat treatment atmosphere is nitrogen.
[0044] The present invention also provides a battery, comprising the silicon-carbon negative electrode material.
[0045] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0046] 1. The silicon-carbon negative electrode material of the present invention contains Si@CR s O t / B, which makes the specific surface area and D50 of the silicon-carbon negative electrode material better, thereby improving the electrochemical performance.
[0047] 2. The present invention is used to prepare Si@CR s O t In / B, the stability of the obtained composite is improved by blending silica sol, graphite powder and boric acid polymer (BAP). The main reason is that BAP molecules contain NB internal coordination bonds. Silica sol, graphite powder and ABP are blended to obtain Si@CR s O t / B, after heat treatment, the lamellar structure is more obvious, the block structure is less, the lamellar structure has a larger surface area, is less affected by volume changes, and has more contact points, so the ion diffusion method is optimized ( Figure 1-3 In the SEM image, compared with the comparative example), the cycle performance and rate performance are better than those of the comparative example, indicating that the performance improvement effect of the silicon-carbon negative electrode material containing BAP is more obvious.
[0048] 3. The present invention adds acid and a reducing agent to leach the battery black powder to obtain an insoluble slag mainly containing graphite. The obtained graphite powder can be used for two purposes, thereby reducing the preparation cost. On the one hand, it can be used for Li f - Si@CR s O t / BZ a O b On the one hand, it can be used as a carbon source in the lithium-ion battery, and on the other hand, it can be used as a cathode material for electrolysis in lithium insertion process. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1This is a SEM image of the silicon-carbon negative electrode material of Example 3 of the present invention;
[0050] Figure 2 This is a SEM image of the silicon-carbon negative electrode material of Comparative Example 2 of the present invention;
[0051] Figure 3 This is a graph of the 1st to 100th discharge specific capacity of Examples 1 and 3 of the present invention and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0052] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0053] Example 1
[0054] The silicon-carbon negative electrode material of this embodiment has a chemical formula of Li 0.02 - Si@C-ZrO2 / B-Al2O3.
[0055] The preparation method of the silicon-carbon negative electrode material of this embodiment has the following specific steps:
[0056] (1) Graphite powder: 150 g of battery black powder was obtained by pyrolysis and sieving of NCM power batteries. 1.5 L of 2.63 mol / L sulfuric acid was added to adjust the pH to 0.02. 20 g of sodium sulfite was added, stirred, and filtered to obtain 34 g of insoluble residue. The residue was washed with water until neutral. 4 g of the insoluble residue was mixed with 20 ml of glycerol and sent to a pulverizer to be pulverized to obtain graphite powder. The graphite powder had a particle size of <5 μm and was pressed with a powder tablet press to obtain long flake graphite.
[0057] (2) Preparation of flaky Si@C-ZrO2 / B: 40 g silica sol (silicon dioxide content 27.3%), 0.3 g zirconium sulfate and 0.3 ml 4-borate-4',4'-dimethyltriphenylamine were mixed and stirred with an ultrasonic mixer, and 3 g graphite powder was added during the process to obtain a homogeneous Si@C-Zr(SO4)2 / 4-borate-4',4'-dimethyltriphenylamine precursor, which was dried in an oven at 115°C to constant weight, then heated at 210°C under nitrogen for 5 h, cooled, and washed to obtain 10 g black powder Si@C-ZrO2 / B;
[0058] (3) The lithium ion conductor membrane is used to separate the electrolytic cell into two half cells (cathode half cell and anode half cell). The electrode in the cathode half cell is cathode graphite. 10g of Si@C-ZrO2 / B material is attached to the graphite and 400ml of conductive agent (dimethyl ethylene glycol: ethylene carbonate: 1.5M lithium hexafluorophosphate is mixed in a volume ratio of 1:1.5:1). The electrode in the anode half cell is aluminum sheet. The electrolyte in the anode half cell is 400ml of 0.064mol / L Li2SiO3. The power is turned on for 25min to perform lithium insertion treatment. The cathode half cell is solid-liquid separated, the solid is washed and dried in an oven at 115℃ to obtain 10.2gLi 0.02 - Si@C-ZrO2 / B;
[0059] (4) Add 0.37M lithium hydroxide to the electrolyte in the anode half tank to obtain a precipitate. After solid-liquid separation, the solid is Al(OH)3. Mix 0.3gAl(OH)3 with 8gLi 0.02 - Si@C-ZrO2 / B was mixed evenly and then heated at 219℃ for 3h under nitrogen atmosphere to obtain the silicon-carbon negative electrode material Li 0.02 - Si@C-ZrO2 / B-Al2O3.
[0060] The lithium insertion chemical reaction process of this embodiment is:
[0061] 0.03·1 / 2Li2SiO3+Si@C-ZrO2 / B+0.03·1 / 3Al→Li 0.02 -Si@C-ZrO2 / B+0.03·1 / 3Al 3+ +0.01·1 / 2Li2SiO3.
[0062] Example 2
[0063] The silicon-carbon negative electrode material of this embodiment has a chemical formula of Li 0.02 -Si@C-NiO / B-Al2O3.
[0064] The preparation method of the silicon-carbon negative electrode material of this embodiment has the following specific steps:
[0065] (1) Graphite powder: 150 g of battery black powder was obtained by pyrolysis and sieving of NCM power batteries. 1.5 L of 2.63 mol / L sulfuric acid was added to adjust the pH to 0.02. 25 g of sodium sulfite was added, stirred, and filtered to obtain 34 g of insoluble residue. The residue was washed with water until neutral. 4 g of the insoluble residue was mixed with 20 ml of glycerol and sent to a pulverizer to be pulverized to obtain graphite powder. The graphite powder had a particle size of <5 μm and was pressed with a powder tablet press to obtain long flake graphite.
[0066] (2) Preparation of flaky Si@C-NiO / B: 45 g silica sol (silicon dioxide content 27.3%), 0.2 g nickel sulfate and 0.3 ml 4-borate-4',4'-dimethyltriphenylamine were mixed and stirred with an ultrasonic mixer, and 4 g graphite powder was added during the process to obtain a homogeneous Si@C-NiSO4 / 4-borate-4',4'-dimethyltriphenylamine precursor, which was dried in an oven at 115°C to constant weight, then heated at 210°C under nitrogen for 5 h, cooled, and washed to obtain 10 g black powder Si@C-NiO / B;
[0067] (3) The lithium ion conductor membrane is used to separate the electrolytic cell into two half cells (cathode half cell and anode half cell). The electrode in the cathode half cell is cathode graphite. 10g of Si@C-NiO / B material is attached to the graphite and 400ml of conductive agent (dimethyl ethylene glycol: ethylene carbonate: 1.5mol / L lithium hexafluorophosphate is mixed in a volume ratio of 1:1.5:1). The electrode in the anode half cell is aluminum sheet. The electrolyte in the anode half cell is 400ml 0.064mol / L Li2SiO3. The power is turned on for 35min to perform lithium insertion treatment. The cathode half cell is solid-liquid separated, the solid is washed, and dried in an oven at 115℃ to obtain 10.2gLi 0.02 - Si@C-NiO / B;
[0068] (4) Add 0.37M lithium hydroxide to the electrolyte in the anode half tank to obtain a precipitate. After solid-liquid separation, the solid is Al(OH)3. Mix 0.3gAl(OH)3 with 8gLi 0.02 - Si@C-NiO / B was mixed evenly and then heated at 219℃ for 3h under nitrogen atmosphere to obtain the silicon-carbon negative electrode material Li 0.02 - Si@C-NiO / B-Al2O3.
[0069] Example 3
[0070] The silicon-carbon negative electrode material of this embodiment has a chemical formula of Li 0.03 -Si@C-MnO / B-MgO.
[0071] The preparation method of the silicon-carbon negative electrode material of this embodiment has the following specific steps:
[0072] (1) Graphite powder: Recycle NCM power batteries, pyrolyze and sieve to obtain 150 g of battery black powder, add 1.5 L of 2.63 mol / L sulfuric acid to adjust the pH to 0.02, then add 28 g of sodium sulfite, stir and filter to obtain 34 g of insoluble residue, wash with water until neutral, mix 4 g of insoluble residue with 20 ml of glycerol, send to a pulverizer and pulverize to obtain graphite powder, the particle size of the graphite powder is less than 5 μm, and press with a powder tablet press to obtain long flake graphite;
[0073] (2) Preparation of flake Si@C-MnO / B: 45 g silica sol (silicon dioxide content 27.3%), 0.4 g manganese sulfate and 0.4 ml 4-borate-4',4'-dimethyltriphenylamine were mixed and stirred with an ultrasonic mixer, and 3 g graphite powder was added during the process to obtain a homogeneous Si@C-NiSO4 / 4-borate-4',4'-dimethyltriphenylamine precursor, which was dried in an oven at 115°C to constant weight, then heated at 260°C under nitrogen for 4 h, cooled, and washed to obtain 13 g black powder Si@C-NiO / B;
[0074] (3) The lithium ion conductor membrane is used to separate the electrolytic cell into two half cells (cathode half cell and anode half cell). The electrode in the cathode half cell is cathode graphite. 10g of Si@C-NiO / B material is attached to the graphite and 480ml of conductive agent (dimethyl ethylene glycol: ethylene carbonate: 1.5mol / L lithium hexafluorophosphate is mixed in a volume ratio of 1:1.5:1). The electrode in the anode half cell is aluminum sheet. The electrolyte in the anode half cell is 480ml of 0.087mol / L Li2SiO3. The power is turned on for 48 minutes to perform lithium insertion treatment. The cathode half cell is solid-liquid separated, the solid is washed, and dried in an oven at 115°C to obtain 10.2gLi 0.02 - Si@C-NiO / B;
[0075] (4) Add 0.18 mol / L lithium hydroxide to the electrolyte in the anode half tank to obtain a precipitate. After solid-liquid separation, the solid is Mg(OH)2. Mix 0.22 g Mg(OH)2 with 9 g Li 0.02 - Si@C-NiO / B was mixed evenly and then heated at 286℃ for 2h under nitrogen atmosphere to obtain the silicon-carbon negative electrode material Li 0.03 -Si@C-MnO / B-MgO.
[0076] Example 4
[0077] The silicon-carbon negative electrode material of this embodiment has a chemical formula of Li 0.03 -Si@C-MnO / B-MgO.
[0078] The preparation method of the silicon-carbon negative electrode material of this embodiment has the following specific steps:
[0079] (1) Graphite powder: Recycle NCM power batteries, pyrolyze and sieve to obtain 150 g of battery black powder, add 1.5 L of 2.63 mol / L sulfuric acid to adjust the pH to 0.02, then add 32 g of sodium sulfite, stir and filter to obtain 34 g of insoluble residue, wash with water until neutral, mix 4 g of insoluble residue with 20 ml of glycerol, send to a pulverizer and pulverize to obtain graphite powder, the particle size of the graphite powder is less than 5 μm, and press with a powder tablet press to obtain long flake graphite;
[0080] (2) Preparation of flake Si@C-CuO / B: 45 g silica sol (silicon dioxide content 27.3%), 0.15 g copper chloride and 0.4 ml 4-boric acid ester-4',4'-dimethyltriphenylamine were mixed and stirred with an ultrasonic mixer, and 3 g graphite powder was added during the process to obtain a homogeneous Si@C-CuCl2 / B, B'-thiophene [3,2-B] thiophene-2,5-diacyl bis [boric acid] precursor, which was dried in an oven at 115°C to constant weight, then heated at 260°C under nitrogen for 4 h, cooled, and washed to obtain 11 g black powder Si@C-CuO / B;
[0081] (3) The lithium ion conductor membrane is used to separate the electrolytic cell into two half cells (cathode half cell and anode half cell). The electrode in the cathode half cell is cathode graphite. 10g of Si@C-NiO / B material is attached to the graphite and 480ml of conductive agent (dimethyl ethylene glycol: ethylene carbonate: 1.5mol / L lithium hexafluorophosphate is mixed in a volume ratio of 1:1.5:1). The electrode in the anode half cell is aluminum sheet. The electrolyte in the anode half cell is 480ml of 0.087mol / L Li2SiO3. The power is turned on for 48 minutes to perform lithium insertion treatment. The cathode half cell is solid-liquid separated, the solid is washed, and dried in an oven at 115°C to obtain 10.4gLi 0.04 - Si@C-CuO / B;
[0082] (4) Add 0.18 mol / L lithium hydroxide to the electrolyte in the anode half tank to obtain a precipitate. After solid-liquid separation, the solid is Mg(OH)2. Mix 0.37 g Mg(OH)2 with 8 g Li 0.02 - Si@C-NiO / B was mixed evenly and then heated at 360℃ for 2h under nitrogen atmosphere to obtain the silicon-carbon negative electrode material Li 0.04 -Si@C-CuO / B-MgO.
[0083] Comparative Example 1 (No lithium insertion treatment)
[0084] The silicon-carbon negative electrode material of this comparative example has a chemical formula of Li 0.02 - Si@C-ZrO2 / B-Al2O3.
[0085] The preparation method of the silicon-carbon negative electrode material of this comparative example comprises the following specific steps:
[0086] (1) Graphite powder: 150 g of battery black powder was obtained by pyrolysis and sieving of NCM power batteries. 1.5 L of 2.63 mol / L sulfuric acid was added to adjust the pH to 0.02. 25 g of sodium sulfite was added, stirred, and filtered to obtain 34 g of insoluble residue. The residue was washed with water until neutral. 4 g of the insoluble residue was mixed with 20 ml of glycerol and sent to a pulverizer to be pulverized to obtain graphite powder. The graphite powder had a particle size of <5 μm and was pressed with a powder tablet press to obtain long flake graphite.
[0087] (2) Preparation of flaky Si@C-ZrO2 / B: 40 g of silica sol (silicon dioxide content: 27.3%), 0.3 g of zirconium sulfate and 0.3 ml of 4-borate-4',4'-dimethyltriphenylamine were mixed and stirred in an ultrasonic mixer, and 3 g of graphite powder was added during the process to obtain a homogeneous Si@C-Zr(SO4)2 / 4-borate-4',4'-dimethyltriphenylamine precursor. The precursor was dried in an oven at 115°C to constant weight, heated at 210°C in a nitrogen atmosphere for 5 h, cooled and washed to obtain 10 g of black powder Si@C-ZrO2 / B.
[0088] Comparative Example 2 (without addition of boric acid polymer)
[0089] The silicon-carbon negative electrode material of this comparative example has a chemical formula of Li 0.03 -Si@C-MnO / B-MgO.
[0090] The preparation method of the silicon-carbon negative electrode material of this comparative example comprises the following specific steps:
[0091] (1) Graphite powder: 150 g of battery black powder was obtained by pyrolysis and sieving of NCM power batteries. 1.5 L of 2.63 mol / L sulfuric acid was added to adjust the pH to 0.02. 20 g of sodium sulfite was added, stirred, and filtered to obtain 34 g of insoluble residue. The residue was washed with water until neutral. 4 g of the insoluble residue was mixed with 20 ml of glycerol and sent to a pulverizer to be pulverized to obtain graphite powder. The graphite powder had a particle size of <5 μm and was pressed with a powder tablet press to obtain long flake graphite.
[0092] (2) Preparation of flake Si@C-MnO / B: 45 g silica sol (silicon dioxide content 27.3%), 0.4 g manganese sulfate and 0.4 ml 4-borate-4',4'-dimethyltriphenylamine were mixed and stirred with an ultrasonic mixer, and 3 g graphite powder was added during the process to obtain a homogeneous Si@C-MnSO4 / 4-borate-4',4'-dimethyltriphenylamine precursor, which was dried in an oven at 115°C to constant weight, then heated at 260°C under nitrogen for 4 h, cooled, and washed to obtain 13 g black powder Si@C-MnO / B;
[0093] (3) The lithium ion conductor membrane is used to separate the electrolytic cell into two half cells (cathode half cell and anode half cell). The electrode in the cathode half cell is cathode graphite. 10g of Si@C-MnO / B material is attached to the graphite, and 480ml of conductive agent (dimethyl ethylene glycol: ethylene carbonate: 1.5mol / L lithium hexafluorophosphate is mixed in a volume ratio of 1:1.5:1) is added. The electrode in the anode half cell is an aluminum sheet. The electrolyte in the anode half cell is 480ml of 0.087mol / L Li2SiO3. The power is turned on for 48 minutes to perform lithium insertion treatment. The cathode half cell is solid-liquid separated, the solid is washed, and dried in an oven at 115°C to obtain 10.2gLi 0.02 - Si@C-MnO / B;
[0094] (4) Add 0.18 mol / L lithium hydroxide to the electrolyte in the anode half tank to obtain a precipitate. After solid-liquid separation, the solid is Mg(OH)2. Mix 0.22 g Mg(OH)2 with 9 g Li 0.02 - Si@C-MnO was mixed evenly and then heated at 286℃ for 2h under nitrogen atmosphere to obtain the silicon-carbon negative electrode material Li 0.03 -Si@C-MnO-MgO.
[0095] Analysis of Examples 1-4 and Comparative Examples 1-2:
[0096] Figure 1 This is the SEM image of the silicon-carbon negative electrode material of Comparative Example 2. It can be seen that the silicon-carbon negative electrode material Li prepared in Comparative Example 3 0.03 -Si@C-MnO-MgO is mostly in the form of blocks and flakes. The size of the block-shaped silicon-carbon negative electrode material is about 5μm. Figure 2 The SEM image of the silicon-carbon negative electrode material of Example 3 shows that the silicon-carbon negative electrode material Li prepared in Example 3 0.03 -Si@C-MnO / B-MgO has more flakes and fewer fast shapes. The size of the flake silicon-carbon negative electrode material is about 400-800nm.
[0097] Table 1 shows the specific surface area and D50 of the silicon-carbon negative electrode materials of Examples 1-3 and Comparative Examples 1 and 2. The specific surface area and D50 of the silicon-carbon negative electrode materials prepared in Examples 1-3 are better than the specific surface area and D50 of the silicon-carbon negative electrode materials of Comparative Examples 1 and 2. In addition, the specific surface area of the silicon-carbon negative electrode material prepared in Comparative Example 1 is higher than the specific surface area of the silicon-carbon negative electrode material of Comparative Example 2, and the D50 of the silicon-carbon negative electrode material prepared in Comparative Example 1 is higher than the D50 of the silicon-carbon negative electrode material of Comparative Example 2, indicating that the specific surface area and D50 of the silicon-carbon negative electrode material after adding boric acid polymer (BAP) are better than those of the silicon-carbon negative electrode material prepared in Comparative Example 1. 50 Better.
[0098] Analysis of Examples 1, 3 and Comparative Examples 1, 2:
[0099] The electrode was prepared by an electrochemical method. First, the pole piece was prepared: the silicon-carbon negative electrode active material, Super P conductive agent, and binder prepared in Example 1, Example 3, Comparative Examples 1 and 2 were weighed with an electronic balance according to a mass ratio of 8:1.5:0.5, placed in a specific weighing bottle, and dispersed evenly. Ultrapure water was used as a solvent, and the slurry was mixed with a magnetic stirrer. The prepared slurry was then coated with a coater. The current collector was made of copper foil and placed in a drying oven at 85°C for 8 hours. Finally, the slicer was used to slice the pole piece with a diameter of about 12 mm, which could be used for electrochemical testing.
[0100] Button cell assembly: calculate the active material loading of the electrode, transfer the electrode to the glove box, prepare to stack the electrode shell, silicon negative electrode, diaphragm, metal lithium counter electrode, and nickel foam in order, and then assemble the button cell. After the half-cell is assembled, it is pressure packaged. After packaging, the button cell needs to be placed at room temperature overnight. During the test, the test environment is kept at room temperature (15-25℃), the voltage range is 0.001-1.5V, the current density is set to 0.5A / g, 1A / g, 1.5A / g, 3A / g, and the number of cycles is 100 times, see Figure 3 .
[0101] Table 1 Specific surface area and conductivity of silicon-carbon negative electrode of Examples 1-4 and Comparative Examples 1-2
[0102] Group <![CDATA[BET(m 2 / g)]]> <![CDATA[D 90 (μm)]]> <![CDATA[D 50 (μm)]]> Example 1 0.481 1.22 0.69 Example 2 0.468 1.24 0.68 Example 3 0.446 1.01 0.64 Example 4 0.455 1.33 0.67 Comparative Example 1 0.363 1.56 0.83 Comparative Example 2 0.247 7.43 3.73
[0103] Figure 3 The 1st to 100th discharge capacity diagrams of Examples 1 and 3 and Comparative Examples 1 and 2, combined with Table 1 and Figure 3 , at a current density of 0.5A / g, the first discharge specific capacities of Examples 1 and 3 reached 2259mAh / g and 2647mAh / g, respectively, and the first discharge specific capacities of Comparative Examples 1 and 2 reached 1798mAh / g and 2302mAh / g, respectively. At a current density of 3A / g, when the number of cycles reached 31 times, the discharge specific capacities of Examples 1 and 3 reached 1473mAh / g and 1289mAh / g, respectively, and the discharge specific capacities of Comparative Examples 1 and 2 at the 31st time were 601mAh / g and 1018mAh / g, respectively. Examples 1 and 3 exhibited excellent rate and cycle performance. The specific surface area, D 50 , D 90 The specific surface area and D of the silicon-carbon negative electrode prepared in Comparative Examples 1-2 are better than those in Comparative Examples 1-2. 50 , D 90 , especially the specific surface area, D 50 , D 90 The specific surface area and D of the silicon-carbon negative electrode prepared in ratio 1 are higher than those obtained in ratio 1. 50 , D90 , indicating that the performance of silicon-carbon negative electrode treated with boric acid polymer (BAP) is better.
[0104] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A silicon-carbon negative electrode material, characterized in that: The chemical formula of the silicon-carbon negative electrode material is Li f - Si@CR s O t / BZ a O b ; R is at least one of zirconium, copper, nickel, cobalt, manganese, chromium, titanium, molybdenum, silver, magnesium, calcium, germanium, tin, and antimony; Z is at least one of aluminum, magnesium, and zinc, wherein s and t are independently 1, 2, 3, 4, or 5, a=1 or 2, b=1 or 3, and f=0.02, 0.03, or 0.04; The silicon-carbon negative electrode material is prepared by the following steps: The silica sol, soluble R salt and boric acid polymer are mixed and stirred, and then graphite powder is added and mixed to obtain Si@CR salt / BAP precursor, and then heat treated to obtain Si@CR s O t / B; In an electrolytic cell with graphite block as cathode and metal Z as anode, a lithium ion conductor membrane is used to separate the electrolytic cell into two half cells, namely the cathode half cell and the anode half cell. s O t / B is placed in the cathode half tank and powered for electrolysis to carry out lithium insertion treatment, the cathode half tank is separated into solid and liquid, the solid is washed and dried to obtain Li f - Si@CR s O t / B; Add lithium source to the electrolyte in the anode half tank, stir, react, separate solid and liquid, take the solid phase and the Li f - Si@CR s O t / B are mixed evenly, and then heat treated to obtain the silicon-carbon negative electrode material; Wherein, the BAP is a boric acid polymer.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The Z a O b It is one of Al2O3, MgO and ZnO.
3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The R s O t It is at least one of ZrO2, NiO, MnO, and CuO.
4. The silicon-carbon negative electrode material according to claim 1, characterized in that: The silicon-carbon negative electrode material is Li 0.04 - Si@C-CuO / B-MgO、Li 0.03 - Si@C-MnO / B-MgO、Li 0.02 - Si@C-ZrO2 / B-Al2O3、Li 0.02 - At least one of Si@C-NiO / B-Al2O3.
5. The method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 4, characterized in that: The preparation method is used to prepare the silicon-carbon negative electrode material according to any one of claims 1 to 4.
6. The method for preparing the silicon-carbon negative electrode material according to claim 5, characterized in that: The following steps are involved: The silica sol, soluble R salt and boric acid polymer are mixed and stirred, and then graphite powder is added and mixed to obtain Si@CR salt / BAP precursor, and then heat treated to obtain Si@CR s O t / B; In an electrolytic cell with graphite block as cathode and metal Z as anode, a lithium ion conductor membrane is used to separate the electrolytic cell into two half cells, namely the cathode half cell and the anode half cell. s O t / B is placed in the cathode half tank and powered for electrolysis to carry out lithium insertion treatment, the cathode half tank is separated into solid and liquid, the solid is washed and dried to obtain Li f - Si@CR s O t / B; Add lithium source to the electrolyte in the anode half tank, stir, react, separate solid and liquid, take the solid phase and the Li f - Si@CR s O t / B are mixed evenly, and then heat treated to obtain the silicon-carbon negative electrode material; Wherein, the BAP is a boric acid polymer.
7. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: The graphite block is prepared by the following method: recovering power batteries, pyrolyzing and screening to obtain battery black powder, adding sulfuric acid to adjust the pH, adding a reducing agent for stirring, separating the solid and liquid, washing the solid phase with water, adding a dispersant for mixing, crushing, and pressing to obtain a graphite block.
8. The method for preparing the silicon-carbon negative electrode material according to claim 7, characterized in that: The reducing agent is at least one of sodium pyrosulfate, potassium pyrosulfate, sodium sulfite, potassium sulfite, sodium thiosulfate, and potassium thiosulfate; the dispersant is at least one of protein solution, glycerol, and benzoic acid.
9. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: The soluble R salt is at least one of soluble sulfates, nitrates, phosphates, chlorides and bromides of zirconium, copper, nickel, cobalt, manganese, chromium, titanium, molybdenum, silver, magnesium calcium, germanium, tin and antimony; the boric acid polymer is at least one of 4-borate-4',4'-dimethyltriphenylamine and B,B'-thiophene [3,2-B]thiophene-2,5-diacylbis [boric acid]; the lithium source is at least one of lithium hydroxide, lithium chloride, lithium sulfate and lithium nitrate.
10. A battery, characterized in that: Comprising the silicon-carbon negative electrode material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Electrolyte adaptive to silicon-carbon negative electrode and lithium ion battery
CN111048834A
Graphite@SiOx@C composite negative electrode material and preparation method and application thereof
CN112331851A